Bird Biodiversity In The Mangrove Ecosystem Of Pannikiang Island, Balusu District, Barru District - Makkatenni, Makkatenni; Jalil, Jalil (Jurnal Biologi Tropis, 2026)
Pannikiang Island, situated within the Barru Regency, is a diminutive landmass predominantly characterized by mangrove flora and serving as a habitat for a diverse array of avian and chiropteran species. This investigation, undertaken from August to October 2024, was designed to ascertain the population density, species richness, and conservation standing of the birdlife inhabiting Pannikiang Island. Employing an exploratory research methodology, data were systematically gathered utilizing the Point Count technique across two designated observation points. The analysis of species heterogeneity was conducted through the application of the Shannon-Wiener Index formula, while species equitability was assessed according to the criteria established by Odum (1971). The findings revealed the presence of 30 distinct bird species within the mangrove ecosystem, with 28 species identified at station 1 and 22 species at station 2. The calculated diversity index for avian populations stood at 2.44 at station 1 and 2.77 at station 2, both values falling within the intermediate range of diversity. The Shannon's evenness index (E) for species distribution at observation station 1 was determined to be 0.82, while at station 2, it was recorded as 0.79. These values indicate a high degree of uniformity in species composition across both locations, suggesting that most avian species observed are present at all sampling sites. Furthermore, two species, the Oriental Darter (Anhinga melanogaster) and the Greater      Adjutant (Mycteria cinerea), are identified as protected under the         Indonesian Minister of Environment and Forestry Regulation No. P.106/MENLHK/SETJEN/KUM.1/12/2018. Globally, the International Union for Conservation of Nature (IUCN) classifies both of these species as Near Threatened (NT), indicating a heightened risk of endangerment in the wild.